The bacteria of Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) are site-specific and distinct from freshwater environment - Zhang, Xizhao; Ying, Congping; Jiang, Min; Lin, Danqing; You, Lei; Yin, Denghua; Zhang, Jialu; Liu, Kai; Xu, Pao (Frontiers in Microbiology, 2022)
Bacteria play an essential role in the health of marine mammals, and the bacteria of marine mammals are widely concerned, but less is known about freshwater mammals. In this study, we investigated the bacteria of various body sites of Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) and analyzed their association with freshwater environmental bacteria. The bacterial community and function of Yangtze finless porpoise showed apparent site-specificity. Various body sites have distinct differences in bacteria and have their dominant bacteria. Romboutsia, Plesiomonas, Actinobacillus, Candidatus Arthromitus dominated in the intestine (fecal and rectal samples). Fusobacterium, Streptococcus, and Acinetobacter dominated in the oral. The dominant genera in the blowhole include Suttonella, Psychrobacter, and two uncultured genera. Psychrobacter, Flavobacterium, and Acinetobacter were dominant in the skin. The alpha diversity of intestinal (fecal and rectal) bacteria was the lowest, while that of skin was the highest. The oral and skin bacteria of Yangtze finless porpoise significantly differed between the natural and semi-natural conditions, but no gender difference was observed. A clear boundary was found between the animal body sites and the freshwater environmental bacteria. Even the skin bacteria, which are more affected by the environment, are significantly different from the environmental bacteria and harbor indigenous bacteria. Our results provide a comprehensive preliminary exploration of the bacteria of Yangtze finless porpoise and its association with bacteria in the freshwater environment.